How did the AD 1755 tsunami impact on sand barriers across the southern coast of Portugal? - Costa, Pedro (2017)
Tsunamis are highly energetic events that may destructively impact the coast. Resolving the degree of coastal resilience to tsunamis is extremely difficult and sometimes impossible. In part, our understanding is constrained by the limited number of contemporaneous examples and by the high dynamism of coastal systems. In fact, longterm changes of coastal systems can mask the evidence of past tsunamis, leaving us a short or incomplete sedimentary archive. Here, we present a multidisciplinary approach involving sedimentological, geomorphological and geophysical analyses and numerical modelling of the AD 1755 tsunami flood on a coastal segment located within the southern coast of Portugal. In particular, the work focuses on deciphering the impact of the tsunami waves over a coastal sand barrier enclosing two lowlands largely inundated by the tsunami flood. Erosional features documented by geophysical data were assigned to the AD 1755 eventwith support of sedimentological and age estimation results. Furthermore, these features allowed the calibration of the simulation settings to reconstruct the local conditions and establish the run-up range of the AD 1755 tsunami when it hit this coast (6– 8 m above mean sea level). Our work highlights the usefulness of erosional imprints preserved in the sediment record to interpret the impact of the extreme events on sand barriers